Association between Nutritional Status and Intelligence Quotient of Junior High School Students in Denpasar - Ni Made Septiari Maryani Ardi; I Wayan Gede Artawan Eka Putra; Gede Ngurah Indraguna Pinatih (Universitas Udayana, 2016)
Background and purpose: The prevalence of obesity among youth in Indonesia was increasing. Obese young people have risk of having noncommunicable disease and also affect the intelligence quotient. This study aims to determine the association between nutritional status and intelligence quotient among junior high school students. Methods: The study was cross sectional with a sample of 176 respondents determined by simple random sampling. Data were collected through an IQ test using Standard Progressive Matrices method, weight and height measurement, and self-administered questionnaires. Data were analysed using Stata. Bivariate analysis using chi-square test and multivariate by poisson regression test. Results: Mean age of respondents was 12.2 years and mean of IQ was 105.8. There were 77 obese students, consisting of 48 (62.3%) males and 29 (37.7%) females. 47 students (26.7%) indicated a below average IQ, consisting of 24 (51.1%) males and 23 (48.9%) females. Bivariate analysis indicated that 55.8% of obese students had below average IQ meanwhile students with a normal nutritional status of 4,0%. On below average IQ 4.0% students never had obesity; 56.8% students <6 years of being obese and 67.5% students ≥6 years of being obese. Multivariate analysis found that respondent’s intelligence quotient was associated with obesity (APR=6.6; 95%Cl: 2.0-21.5). Conclusion: Intelligence quotient was significantly associated with obesity and the period of obesity. The longer the period of being obese more likely had a below average IQ.